Concentration Dependent Studies on the Laser-Induced Mid-Infrared Emission from KCl-NaCl Tablets - Oyebola, Olusola; Hommerich, Uwe; Brown, Ei EI; Yang, Clayton; Trivedi, S; Samuels, Alan; Snyder, Peter (Photonics Letters of Poland, 2011)
Laser Induced Breakdown Spectroscopy (LIBS) is a technique for determining the elemental composition of a chemical substance. Pumping with a 1064nm Nd:YAG pulse laser, mid-infrared emissions from LIBS plasma produced from KCl were examined between 2.0µm and 4.5µm, with atomic emission lines observed at 2.72µm, 3.15µm, 3.77µm and 4.05µm for potassium, consistent with NIST atomic spectra database. With further focus on the 2.72µm emission, detection limit studies were carried on different concentration samples of KCl_NaCl mix, to determine the detection limit of potassium (K). A limit of detection of 0.19wt%/wt was obtained for potassium in the mid-IR region. Full Text: PDF References D.A. Cremers, L.J. Radziemski, "123456", Handbook of Laser-Induced Breakdown Spectroscopy (John Wiley, 2006)[CrossRef] C. Pasquini, J. Cortez, L.M. C. Silva, F.B. Gonzaga, "Laser Induced Breakdown Spectroscopy", J. Braz. Chem. Soc. 18, 463 (2007)[CrossRef] L.J. Radziemski, D.A. Cremers, M. Bostian, R.C. Chinni, C. Navarro-Northrup, "Laser-Induced Breakdown Spectra in the Infrared Region from 750 to 2000 nm Using a Cooled InGaAs Diode Array Detector", App. Spectroscopy 61, 1141 (2007)[CrossRef] C.S.-C. Yang, E.E. Brown, U.H. Hommerich, S.B. Trivedi, A.C. Samuels, A.P. Snyder, "Mid-Infrared Emission from Laser-Induced Breakdown Spectroscopy", App. Spectroscopy 61, 321 (2007)[CrossRef] C.S.-C. Yang, E.E. Brown, U.H. Hommerich, S.B. Trivedi, A.C. Samuels, A.P. Snyder, "Mid-Infrared Laser-Induced Breakdown Spectroscopy Emissions from Alkali Metal Halides", App. Spectroscopy 62, 714 (2008)[CrossRef] W. Tawfik Y. Mohamed, "Improved LIBS limit of detection of Be, Mg, Si, Mn, Fe and Cu in aluminum alloy samples using a portable Echelle spectrometer with ICCD camera", Optics and Laser Techn. 40, 30 (2008)[CrossRef] Potassium Gluconate?Dietary supplement produced by Pharmavite? LLC, purchased as a non-prescription drug at Walgreens. M.A. Ismail, H. Imam, A. Elhassan, W.T. Youniss, M.A. Harith, "LIBS limit of detection and plasma parameters of some elements in two different metallic matrices", J. Anal. At. Spectrom. 19, 489 (2004)[CrossRef]